Mitigatory role of butyrylcholinesterase in freshwater fish Labeo rohita exposed to glyphosate based herbicide Roundup®. (2021) - Geetha, N.
Abstract: The objective of this study was to investigate the toxic effect of Roundup® to freshwater fish Labeo rohita . Fish were exposed to sub-lethal concentration of Roundup® (0.7 mg/L) for 20 days, after stipulated time, plasma electrolytes, biochemical components and enzymes activity were measured. Elevated Butyrylcholinesterase level up to 10th day reduced the stress to fish by binding with active sites of Roundup®, which may contribute to maintain plasma electrolytes and transaminases activity. During its exhaustion phase, except protein all biomarkers level increased significantly (p < 0.05) with that of control. The present study reveals that elevated BChE mitigate the Roundup® induced stress in fish. However, extensive use of this herbicide poses a threat to aquatic organisms.